Transformasi Sistem Pendidikan Islam: Pergulatan Identitas Muslim Melayu-Patani - Fathurahman, Oman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
The book attempts to explain the dynamics of the Islamic education system in Patani, Thailand, from its beginning up to the time when the Malay world, to which Patani belongs, was modernized. A comparison of Islamic education in Patani, with that which exists in other areas such as Indonesia and Malaysa, is complicated, but this is the very reason why it is so interesting. In the context of education, Islam-including the Islam developed in Malay-Patani areas-has played a significant, even a dominant, role. It is the driving force behind the establishment, the development, and the enforcement of educational institutions. Here pondok, pesantren, meunasah, surau and other traditional institutions of education must be mentioned for-in the Malay-Nusantara context they have been instrumental in the whole intellectual renaissance in the region. Rich Islamic traditions were studied and socialized intensively in those institutions and this, in turn, enabled the local ulamas to produce important works in the field of Islamic studies.DOI: 10.15408/sdi.v8i1.699